Advances in the pathogenesis and treatment of Nagashima-type palmoplantar keratosis - LI Kezhen; LU Antong; ZHONG Weilong; YU Bo (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2024)
Nagashima-type palmoplantar keratosis (NPPK) is a relatively common autosomal recessive dermatosis characterized by well-defined diffuse erythema and non-destructive hyperkeratosis on the palmoplantar areas, with swelling and whitening when exposed to water. The pathogenesis of NPPK can be attributable to altered structure and function of SERPINB7, environmental factors, barrier dysfunction and inflammatory response. There is no specific and standardized therapy for this disorder. Topical treatment is primary therapy although systemic drugs or surgery can be used for severe cases. Gentamicin, a targeted therapy for the disease, has shown some potential, but more clinical studies are still needed to verify its efficacy and safety. The aim of this review is to summarize the causative gene, pathogenesis and therapeutic strategies of NPPK.